Innovation as a Factor of the Development of Territorial Communities - V. Varuk, V; O. Kramarenko, A; A. LunovÐ°, V; S. Parkhomenko, O (International Journal of Engineering and Technology, 2018)
The purpose of the paper is to substantiate the need for the introduction of innovations in the activities of business entities and territorial communities. Analyzing, systematizing and generalizing the scientific work of many researchers, it was discovered that innovation is one of the factors of successful decentralization. As a result of the study, the essence of the concept of innovation is shown, which can be considered as the introduction of something "new and improved" or activity that requires a person or community to do something different than before. Elements of innovation capacity are singled out. The peculiarities of investment activity formation in Ukraine are outlined. The basic principles and functions of management of effective work in the field of innovations are determined. The factors of implementation of innovations in the branches, organizations and territorial communities are presented.Â